2007
DOI: 10.1007/s00330-007-0785-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of focal liver lesions by ADC measurements using a respiratory triggered diffusion-weighted single-shot echo-planar MR imaging technique

Abstract: The aim of this study was to determine apparent diffusion coefficients (ADCs) of focal liver lesions on the basis of a respiratory triggered diffusion-weighted single-shot echo-planar MR imaging sequence (DW-SS-EPI) and to evaluate whether ADC measurements can be used to characterize lesions. One hundred and two patients with focal liver lesions [11 hepatocellular carcinomas (HCC), 82 metastases, 4 focal nodular hyperplasias (FNH), 56 hemangiomas and 51 cysts; mean size, 16.6 mm; range 5-92 mm] were examined o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
274
6
9

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 377 publications
(308 citation statements)
references
References 35 publications
19
274
6
9
Order By: Relevance
“…There are several recent reports on the use of respiratory triggered acquisitions for liver DWI (15,16,[28][29][30][31]. However, only two studies have specifically compared different diffusion acquisition schemes for liver imaging (28,30).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are several recent reports on the use of respiratory triggered acquisitions for liver DWI (15,16,[28][29][30][31]. However, only two studies have specifically compared different diffusion acquisition schemes for liver imaging (28,30).…”
Section: Discussionmentioning
confidence: 99%
“…Few recent studies have reported the use of respiratory triggered liver DWI without (28 -30) or with a navigator echo (15,16). Gourtsoyianni et al (29) assessed the accuracy of ADC obtained with non navigator echo respiratory triggered SS EPI DWI sequence (n ϭ 38) for characterization of liver lesions, and found sensitivity and specificity of 100% for diagnosis of malignancy using lesion ADC Ͻ 1.26 ϫ 10 Ϫ3 mm 2 /s, similar to our reported sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations